Catalysts of actual purchase behavior: A theory of planned behavior analysis for local brand products in Tanzania - Mushi, Hellena Mohamedy (Kuala Lumpur International Business, Economics and Law, 2026)
Proceeding – 29th Kuala Lumpur International Business, Economics and Law Conference